2009
DOI: 10.1158/0008-5472.can-08-3370
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Optical Spectroscopy: A Robust Tool for Direct Measurement of Breast Cancer Vascular Oxygenation and Total Hemoglobin Content In vivo

Abstract: We propose the use of a robust, biopsy needle-based, fiberoptic tool for routine clinical quantification of tumor oxygenation at the time of diagnostic biopsy for breast cancer. The purpose of this study was to show diffuse reflectance spectroscopy as a quantitative tool to measure oxygenation levels in the vascular compartment of breast cancers in vivo via an optical biopsy technique. Thirty-five patients undergoing surgical treatment for breast cancer were recruited for the study at Duke University Medical C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
95
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 48 publications
4
95
1
Order By: Relevance
“…Diffuse reflectance spectroscopy (DRS) is one such technique which, when coupled with appropriate light transport models, is capable of extracting quantitative information about tissue absorption and scattering, both of which reflect underlying tissue composition [17][18][19][20][21][22]. Zhu et al characterized the underlying sources of optical contrast in malignant and non-malignant breast tissues that can be exploited for intra-operative margin assessment and her results are very consistent with other similar studies reported in the literature [21,[23][24][25].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Diffuse reflectance spectroscopy (DRS) is one such technique which, when coupled with appropriate light transport models, is capable of extracting quantitative information about tissue absorption and scattering, both of which reflect underlying tissue composition [17][18][19][20][21][22]. Zhu et al characterized the underlying sources of optical contrast in malignant and non-malignant breast tissues that can be exploited for intra-operative margin assessment and her results are very consistent with other similar studies reported in the literature [21,[23][24][25].…”
Section: Introductionsupporting
confidence: 60%
“…The core instrumentation has been previously documented in detail [17,24,25]. To briefly summarize, the system consists of a Xenon arc lamp, spectrograph, and a 2D CCD camera.…”
Section: Introductionmentioning
confidence: 99%
“…We anticipate that DRS-based biopsy guidance, as described in this study, is not limited to lung cancer, but may also be used for breast (9)(10)(11)(12), liver (13), and other cancer types. Larger multicenter studies are needed to confirm our data and further elucidate the diagnostic value (sensitivity and specificity) of the reported method for lung cancer and other tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent analysis of the tissue's spectral response provides specific quantitative morphologic, biochemical, and functional information, thereby enabling tissue discrimination and potentially improving diagnostic capability. Several preclinical and clinical studies have demonstrated the potential use of DRS for cancer detection and diagnosis for a variety of tissue sites (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Despite the proven potential of DRS (19,20), clinical translation involves a variety of major challenges, many of which are unique to this stage of technology development.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrate the feasibility of DRS to differentiate tumors from unaffected parenchyma in different organ systems such as breast [3][4][5][6], lung [7][8][9][10] and brain [11][12][13] both ex vivo and in vivo. The non-invasive optical measurement technique utilizes light absorption and scattering after its interaction with cells and molecules.…”
Section: Introductionmentioning
confidence: 99%